Features of physical development of preschool children - Zavgorodnyaya R.V; Solontsova A.I; Svechkarev I.S; Stanishtvskaya T.I. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2010)
The morphofunctional features of organism of children of primary school age are considered in intercommunication with their somatotype. The inspected contingent was made by 90 practically healthy children in age from 6 to 9 years. The anthropometric signs of children were characterized an increase gravimetric type-high indexes with predominance of asthenic somatotype and increase of normosthenic and hypersthenic to the end of the studied period. Complex anthropometric research of indexes of children allowed to estimate their physical development.